INVESTIGATING THE RELIABILITY, VALIDITY, AND SENSITIVITY OF THE SCALES ASSESSING HEALTH RELATED QUALITY OF LIFE AND FUNCTIONAL HEALTH STATUS IN CEREBRAL PALSY (International Journal of Physiotherapy, 2016)
Background: Cerebral palsy (CP) is the most common cause of physical disability in children and it causes many problems such as motor, sensory and cognitive impairment, and it leads to effect child’s quality of life. There are many of questionnaire for evaluating quality of life but which is reliable, valid and sensitive to age groups children with CP in Turkish. Our study aims to investigate whether the Pediatric Outcomes Data Collection Instrument (PODCI), Pediatric Quality of Life Inventory (PedsQL) and Child Health Questionnaire Parent Form (CHQ PF-50) scales are reliable, valid, and sensitive in children with Cerebral Palsy among different age groups and impairment levels.Methods: 105 children with CP, 48 healthy children and their mothers were participated in this study. They were divided into three groups according to their age; as 2-7 years, 8-12 years and 13-18 years. Statistical power analysis was conducted to acquire statistical power at a medium level (80%).Results: The internal consistency of scales was acceptable and their test-retest reliability was significant (for PODCI, α=0.93 and ICC=0.992, for PedsQL α=0.85 and ICC=0.955, for CHQ PF-50 α=0.92 and ICC=0.975). The findings of their validity indicated that they were significantly sensitive in discriminating healthy children and children with CP (p